Development of Cupcake Production Technology Using Rye Flour - Hovhannisyan, N. G.; Vanoyan, A. P. (ՀԱԱՀ հիմնադրամ)
Functional food production has become relevant, particularly in recent years, related to technical advancement, reduction of physiological energy consumption and imbalance in labor capacity. Healthy diet is one of the most important factors describing the health of country’s population. In this regard development of new technologies for manufacturing new range of flour confectionery products is considered to be quite actual, while functional food production technology is of significant importance from the prospect of food industry development on the whole. The recommended technology can be easily introduced in the production with no need for additional technological equipment.
Keywords: Food Science and Technology